On the Dynamics of One Parameter Family of Functions f_k (x)=kcsc(x) - Hussain, Iman A.; Jamil, Zeana Z.; Hamada, Nuha H. (Iraqi Journal of Science, 2022)
In this research, we study the dynamics of one parameter family of meromorphic functions . Furthermore, we describe the nature of fixed points of the functions in ,and we explain the numbers of real fixed points depending on the critical point . So, we develop some necessary conditions for the convergence of the sequence when .